A newly identified pathology of episodic angioedema with hypereosinophilia (Gleich syndrome) revealed by multiomics analysis - Tatsuya Koreeda, MS; Hirokazu Muraoka, MD, PhD, MPH; Yasunori Sato, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Episodic angioedema with eosinophilia (Gleich syndrome) is a rare disease marked by periodic angioedema, fever, and severe eosinophilia, with limited understanding of its pathogenesis. Objective: We sought to identify pathogenic factors contributing to severe Gleich syndrome through a comprehensive multiomics approach, using whole-genome sequencing (WGS) and RNA sequencing (RNA-seq). Methods: A multiomics analysis was conducted on a 16- to 20-year-old female patient with severe Gleich syndrome, presenting with periodic high fever, extensive urticaria/eczema, and marked eosinophilia. The analysis included WGS and RNA-seq of blood samples. Results: WGS revealed high-impact pathogenic mutations that have the potential to significantly alter gene function in 16 genes, including PR domain containing 16 (gene involved in transcriptional regulation). RNA-seq identified differentially expressed genes linked to immune response regulation and viral defense. Combined z-score analysis of WGS and RNA-seq highlighted angiotensin-converting enzyme as a key gene, with significant downregulation during disease progression that normalized with treatment. IFNG was also implicated. Conclusions: The findings suggest that decreased angiotensin-converting enzyme expression, driven by PR domain containing 16 (gene involved in transcriptional regulation) mutations and altered IFNG expression, may contribute to increased bradykinin levels and activation of the arachidonic acid cascade, leading to the severe inflammation and angioedema characteristic of Gleich syndrome. This study underscores the utility of integrating WGS and RNA-seq data in elucidating the molecular basis of rare diseases and offers a foundation for developing therapeutic strategies for hypereosinophilic syndromes.